Ragam Bentuk, Makna, dan Aplikasi Masdar dalam Bahasa Arab - Muhbib Abdul Wahab (Buletin Al-Turas, 2007)
Masdar (infinitive, verbal noun) is kind of Arabic noun. It has many varieties of forms, meanings, anduunique usings in structural sentences. Hence its important to understand of using of masdar and its applicationin contextual sentences, especially in order to translate text from Arabic into Indonesian. The varieties of masdarmeaning imply a necessary for revitalization of comprehensively understanding masdar in all perspective, not only inmorphological point of view, but also in gramatical and semantical perspective.